Optimal conditions for the catalytic and non-catalytic pyrolysis of water hyacinth. (April 2015) - Hu, Zhifeng; Ma, Xiaoqian; Li, Longjun
Highlights: Particle size, temperature and catalyst affect greatly the water hyacinth pyrolysis. <200 μm is the optimal particle size for water hyacinth to produce syngas. There are more porosity, surface area and crystalline at a higher temperature. 900 °C is the best pyrolysis temperature for water hyacinth to produce syngas. The syngas production can be greatly promoted by catalysts, and KCl is the best one. Abstract: Water hyacinth pyrolysis was carried out in a quartz tube reactor. Different particle sizes, pyrolysis temperatures and catalysts were tested. The product fractional yields, gaseous products, surface morphology and crystal structure were analyzed in order to obtain the optimal pyrolysis condition for producing syngas (CO + H2 ) from water hyacinth. The results indicated that particle size had a significant impact on water hyacinth pyrolysis and among four particle sizes in this paper dp < 200 μm was the optimal particle size for syngas production. Moreover, active surface area, porosity level and crystalline materials increased as the temperature rose and the results showed that among five temperatures in this study 900 °C was the best pyrolysis temperature for producing syngas. In addition, the syngas production levels can be improved if a suitable catalyst is used. The best catalyst was KCl, followed by CaO and MgO.